From clinical expert nurse to part-time clinical nursing instructor: design and evaluation of a competency-based curriculum with structured mentoring: a mixed methods study - Shourangiz Beiranvand; Sima Mohammad Khan Kermanshahi; Robabeh Memarian; Mohammad Almasian (BMC, 2022)
Abstract Background Transition from a clinical expert nurse to a  part time clinical nursing instructor (PTCNI) poses several challenges. Designing a professional development curriculum to facilitate the transition from a clinical expert nurse to a  PTCNI is critical to effective education. A comprehensive competency-based curriculum was developed and implemented with structured mentoring to prepare clinical expert nurses as PTCNIs. Methods A mixed-methods study with a sequential-exploratory approach was conducted in Iran in 2019. In the qualitative phase, Saylor et al.'s (1981) seven-step model was used, consisting of (1) collecting evidence from a systematic review, (2) conducting interviews with learners, (3) setting goals and objectives, (4) design, (5) implementation, (6) evaluation, and (7) feedback. In the quantitative phase, curriculum domains were evaluated. Additionally, the effective professional communication skills module was implemented using a quasi-experimental study with a pre-test post-test single-group design for 5 PTCNIs in a pilot study. Results After integrating the findings of the literature review and field interviews in the analysis stage, a curriculum was developed with a total of 150 h, six modules, and 24 topics. Results of the pilot study showed a significant improvement in the confidence of PTCNIs as a result of the implementation of the effective communication skills module using the mentoring method (t = − 16.554, p = 0.0005). Conclusions This competency-based curriculum was based on the evidence and needs of PTCNIs and provides a complete coverage of their clinical education competencies. It is suggested that managers of educational institutes that offer nursing programs use this curriculum to prepare them in continuing education programs. Further studies are needed to thoroughly evaluate the learning outcomes for students.